2004
DOI: 10.1177/172460080401900107
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Leptin in Multiple Myeloma Patients and Its Relation to Angiogenic and Inflammatory Cytokines

Abstract: Leptin serum levels do not reflect disease severity in MM. However, there seems to be a decrease in leptin following treatment, which may be associated with an alteration in the metabolic state or the chemokine milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
14
0
1
Order By: Relevance
“…Few studies [11, 17, 2426] have investigated the effects of leptin in hematological tumors and found that leptin modestly promotes proliferation of myeloma cell lines, and reduces chemotherapy induced apoptosis in myeloma cell lines, which are in accordance with our results. In addition, Leptin was correlated with ISS stage in patients with multiple myeloma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Few studies [11, 17, 2426] have investigated the effects of leptin in hematological tumors and found that leptin modestly promotes proliferation of myeloma cell lines, and reduces chemotherapy induced apoptosis in myeloma cell lines, which are in accordance with our results. In addition, Leptin was correlated with ISS stage in patients with multiple myeloma.…”
Section: Discussionsupporting
confidence: 91%
“…We found that mature adipocytes could directly stimulate proliferation, accelerate cell cycle, and up-regulate cell cycle related proteins in multiple myeloma cells when cultured together. Several studies [17, 25, 26] have revealed that adipocytes secreted leptin could help tumor cells to proliferate, chemo-resistant, and metastasis via activating pro-tumor pathways. After adding anti-leptin related receptor antibodies, the proliferation of myeloma cells was inhibited, indicating leptin and its receptors were responsible for the pro-tumor effect of adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although adiponectin was a significant predictor for MM risk, we haven't been able to find either a significant association between adiponectin levels and MM prognostic stages or a significant relation between adiponectin levels and prognostic biological parameters such as CRP [1,30], We have also found that MM patients tend to have higher mean leptin levels than controls by univariate analysis, which may reflect their higher degree of obesity. This is in agreement with two previous studies examining much fewer patients (14 and 62 patients) [25,26]. We also report herein that after adjusting for age, gender, and BMI, as well as for multiple comparisons performed, serum leptin levels weren't significantly different between MM patients and controls.…”
Section: Discussionsupporting
confidence: 95%
“…Two previous studies with small number of cases have examined leptin in association with MM [25,26]. No previous study has focused on adiponectin or resistin as predictors of MM and no prior study has explored simultaneously whether adiponectin, leptin, and/ or resistin are associated with MM.…”
Section: Introductionmentioning
confidence: 98%
“…Более того, содержание этого адипокина в крови прямо коррелирует с уровнями иммуноглобулина класса G (IgG) и β 2 -микроглобулина, содержанием плазматических клеток в костном мозге и стадией заболевания (5,34 ± 1,9 нг/мл при I-II стадиях и 7,93 ± 3,38 нг/мл при III стадии). Следует отметить, что содержание лептина в крови больных ММ достоверно снижается после проведения химиотерапии [42]. У больных ММ отмечается повышение содержания в сыворотке крови другого адипокина -хемерина [43].…”
Section: влияние адипоцитов костного мозга на миеломные клеткиunclassified